PERLINDUNGAN HAM BURUH MIGRAN TAK BERDOKUMEN BERDASARKAN HUKUM PERDAGANGAN DAN HUKUM HAM INTERNASIONAL - Sefriani Sefriani (Jurnal Dinamika Hukum, 2013)
Undocumented migran worker violate immigration rule and potentially give damage toward host state. However many persons exploited them, get advantages from illegal status of the worker. Two problems in this research are how does international law protect undocumented migrant worker and what solutions offer to host state to solve undocumented migran worker matter. This thesis employs normative method of research with qualitative analysis. The result of this thesis reveals international law protect undocumented worker without discrimination. Preventive action will be better conducted by host state than enforcementKeywords: undocumented migran worker, illegal, non discrimination